Comparison of success between external and endonasal dacryocystorhinostomy in primary acquired nasolacrimal duct obstruction in Turkish cohort - Bugra Karasu; Gulunay Kiray; Erdem Eris; Irfan Perente; Ali Riza Cenk Celebi (İstanbul Kuzey Klinikleri, 2020)
OBJECTIVE: To evaluate the results and recurrence rates of external and endonasal dacryocystorhinostomy (DCR) surgery in patients with primary acquired nasolacrimal duct obstruction (PANDO) in Turkish Cohort. METHODS: Medical records were reviewed in all patients who underwent surgery for PANDO between January 2010 and September 2014 in a tertiary university hospital retrospectively. The patients were followed up on the first day, first month, third month and sixth month postoperatively. Lacrimal drainage system and recurrence rates were recorded. RESULTS: This study was conducted in 81 patients, 27 of whom were men (33.3%) and 54 were women (66.7%). The mean follow-up time was 30.13+-16.42 months (range 6–62 months). The mean age was 50.51+-12.47 years (range 16 to 77 years). External DCR was used in 44 (66.7%) of the cases and endonasal DCR was used in 37 (45.7%) of the cases. Surgical results of DCR were divided into three groups based on the integrity and openness of the lacrimal drainage pathway in all PANDO patients. Operation success rates of these data revealed that 45 (55.6%) cases were recorded as successful, 20 (24.7%) of the cases were accepted as partially successful and 16 (19.8%) of the cases were deemed as unsuccessful. Based on these data, surgical success rates were found in 38 (86.4%) patients in external DCR and 27 (73%) patients in endonasal DCR. Surgical failure rates were six (13.6%) in external DCR and 10 (27%) in endonasal DCR. There was no statistically significant difference between success rates and recurrences in both groups (p>0.05). CONCLUSION: Endoscopic DCR produced simple, minimally invasive and preferable results compared to external DCR in the Turkish population. Although the success of external DCR is higher and the recurrence is lower than endoscopic DCR, with the outcomes of this study, endoscopic DCR can be tried as the first choice to protect the patient from major surgery and anesthesia in PANDO.